Launching of progression links between UiTM and the University of Essex - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
Associate Professor Dr. Anealka Aziz Hussin, Associate Professor Dr. Nor FazlinMohd Ramli, Dr. Siti Aeisha Joharry, Dr. Syamimi Turiman, Dr. Mohammad Nor Afandi Ibrahim, Mr Ahmad Aminuddin Soopar, and Mr Adi Idham Jailani were delegates of AРB, UITM Shah Alam who participated in a discussion with delegates from University of Essex led by Prof. Anthony Foster, the Vice Chancellor of University of Essex. The meeting was held on 28th September 2022, and was also attended by delegates from UiTM Perak led by Professor Sr. Dr. Md Yusof Hamid.